Estudio comparativo de plataformas cloud computing para arquitecturas orientada a soa en el gad de Urdaneta - Veloz Cárcamo, Jefferson Alexander (2022)
The present research work allows to demonstrate that technological tool affects as a Cloud Computing platform in service-oriented architectures (SOA) of the municipal GAD of Urdaneta, in a way that significantly improves the processes, the quality of the information, and the permanent availability of the data. safely and reliably. It is also necessary to consider that today there are companies dedicated to offering ubiquitous computer solutions that allow maximizing services through the Internet, and thereby reduce the amount of technological resources. The exploratory and field research methodologies were used to demonstrate the need through technical bibliography, concluding that the institution has a basic computer system and the acceptance of the improvement proposed in this work.